Earnings Divergence of Immigrants - Lam, Kit‐Chun; Liu, Pak‐Wai (Journal of Labor Economics, 2002)
From 1981 to 1991 the mean earnings of immigrants fell further behind those of natives in Hong Kong, with the earnings gap widening from 11.3% to 25.5%. Earnings divergence of this magnitude is rather unusual among countries that receive many immigrants. We show that earnings divergence in Hong Kong is mainly due to divergence between skill prices for immigrants' education and for natives' education. Intertemporal shift in the demand for skills caused by economic restructuring in Hong Kong has a differential impact not only on prices of different levels of skill, but also on prices of skills from different sources.